Ricardian Consumers with Keynesian Propensities - Barsky, Robert B.; Mankiw, N. Gregory; Zeldes, Stephen P. (American Economic Review, 1986)
This paper examines Ricardian equivalence in a world in which taxes are not lump sum, but are levied on risky labor income. It shows that the marginal propensity to consume out of a tax cut, coupled with a future income tax increase, can be substantial under plausible assumptions. Indeed, the MPC out of a tax cut can be closer to the Keynesian value that ignores the future tax liabilities than to the Ricardian value that treats future taxes as if they were lump sum.